2002
DOI: 10.1037/0894-4105.16.3.370
|View full text |Cite
|
Sign up to set email alerts
|

Working memory for complex figures: An fMRI comparison of letter and fractal n-back tasks.

Abstract: Abstractn -back letter and fractal tasks were administered to 11 participants during functional magnetic resonance imaging to test process specificity theories of prefrontal cortex (PFC) function and assess task validity. Tasks were matched on accuracy, but fractal n-back responses were slower and more conservative. Maintenance (1-back minus 0-back) activated inferior parietal and dorsolateral PFC, with additional activation in right ventrolateral PFC during letter n-back and left lingual gyrus during fractal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
188
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 276 publications
(203 citation statements)
references
References 62 publications
10
188
1
4
Order By: Relevance
“…Then, we made a list of activated regions from those studies to compare them with the activated areas of the present study. It was found that every activated area found in our study (Table 2) was also reported as a significant activation focus in one or more previous studies of the verbal 2-back task (Awh et al, 1996;Braver et al, 1997;Cohen et al, 1994Cohen et al, , 1997Honey et al, 2000;Jonides et al, 1997;Kim et al, 2002;Nystrom et al, 2000;Ragland et al, 2002;Smith et al, 1996;Veltman et al, 2003).…”
Section: Discussionmentioning
confidence: 54%
“…Then, we made a list of activated regions from those studies to compare them with the activated areas of the present study. It was found that every activated area found in our study (Table 2) was also reported as a significant activation focus in one or more previous studies of the verbal 2-back task (Awh et al, 1996;Braver et al, 1997;Cohen et al, 1994Cohen et al, , 1997Honey et al, 2000;Jonides et al, 1997;Kim et al, 2002;Nystrom et al, 2000;Ragland et al, 2002;Smith et al, 1996;Veltman et al, 2003).…”
Section: Discussionmentioning
confidence: 54%
“…It is known to activate eloquent areas (Broca's and Wernicke's) of speech planning and execution in the dominant, and sometimes non-dominant, hemisphere. The n-back task is a widely-used paradigm (Ragland, et al 2002;Marshall, et al 2004) in studies of working memory brain circuitry, and has been shown to activate a number of areas in the frontal and parietal cortices, in particular the dorsolateralprefrontal cortex (DLPFC). In our implementation of this task a series of letters was displayed one in a time, and subjects were asked to determine if the current letter was the same as that presented two letters previously (2-back).…”
Section: Task Batterymentioning
confidence: 99%
“…In each run subjects performed one block (15 presentations, 3-sec interval, 5 targets per block) each of 0-, 1-, and 2-back tasks for single letters. 30,31 Visual presentation was via fiber-optic goggles (NordicNeuroLab, Bergen, Norway). Subjects responded by dominant index finger via fiberoptic button box (Current Designs, Philadelphia, PA).…”
Section: Neurophysiological Testingmentioning
confidence: 99%